Crystal structure of N′,N′′′-((1E,1′E)-(propane-2,2-diylbis(1H-pyrrole-5,2diyl))bis(methaneylylidene))di(nicotinohydrazide) pentahydrate, C25H24N8O2·5H2O - Zhou Yi; Zhang Min; Xiong Ying (Zeitschrift für Kristallographie - New Crystal Structures)
C25H34N8O7, triclinic, P1‾ $P‾{1}$ (no. 2), a = 7.507(2) Å, b = 8.0276(18) Å, c = 23.653(6) Å, α = 93.062(8)°, β = 97.015(9)°, γ = 99.478(8)°, V = 1391.4(6) Å3, Z = 2, R gt(F) = 0.0473, wR ref(F 2) = 0.1477, T = 273 K.